Komunikasi Sosial Dalam Membangun Ekonomi Kerakyatan - Nono Sungkono; Prasetya Yoga Santoso; Muminto Arief (Jurnal Pustaka Dianmas, 2022)
The phenomenon that occurred in the City of Tangerang, Banten, as designed by the Regional Development Planning Agency (BAPEDA) in forming Thematic Villages with the following details as many as 301 have been formed and 253 are only in the pilot stage, while 186 are in the preparatory stage of being formed. Cooperatives and Small and Medium Enterprises Office in the last nine months has formed more than 400 Small and Medium Enterprises until the formation of Thematic Villages has emerged. Cipadu Jaya Village is one of the villages that is active in nurturing its citizens to be able to build a people's economy, especially Residents of RT 003 RW 03 by managing an area of 600 M2 which is located next to the village. Cucumber, okrak, banana tree plants, cassava, as well as land fisheries cultivation such as catfish, the results of the land management in question can be enjoyed for daily necessities. The theoretical concept used is social communication with the lecture/discussion method as well as face-to-face socialization with residents of RT 003 RW 03, Cipadu Jaya Village, Larangan District, Tangerang City, Banten Province, the result of Community Service is that social communication can improve the people's economy. Jaya, Prohibition District, Tangerang City, Banten Province.